2015
DOI: 10.1088/0004-6256/150/1/6
|View full text |Cite
|
Sign up to set email alerts
|

THE SOLAR NEIGHBORHOOD. XXXVI. THE LONG-TERM PHOTOMETRIC VARIABILITY OF NEARBY RED DWARFS IN THEVRIOPTICAL BANDS

Abstract: We present an analysis of long-term photometric variability for nearby red dwarf stars at optical wavelengths. The sample consists of 264 M dwarfs south of Dec. = +30 with V − K = 3.96-9.16 and M V ≈ 10-20, corresponding to spectral types M2V-M8V, most of which are within 25 pc. The stars have been observed in the V RI filters for ∼4-14 years at the CTIO/SMARTS 0.9m telescope. Of the 238 red dwarfs within 25 pc, we find that only ∼8% are photometrically variable by at least 20 mmag (∼2%) in the V RI bands. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 40 publications
12
43
0
Order By: Relevance
“…G 169-29 (1650+2226), Figure 7: As illustrated in the second panel of Figure 7, and as first reported in Hosey et al (2015), this object shows a remarkable increase in brightness of ∼60 mmag (6%) that now stretches to 15 years in R.…”
Section: Notes On Individual Systemssupporting
confidence: 73%
See 2 more Smart Citations
“…G 169-29 (1650+2226), Figure 7: As illustrated in the second panel of Figure 7, and as first reported in Hosey et al (2015), this object shows a remarkable increase in brightness of ∼60 mmag (6%) that now stretches to 15 years in R.…”
Section: Notes On Individual Systemssupporting
confidence: 73%
“…The right panel shows the long-term increasing brightness of G 169-29, originally presented in Hosey et al (2015). Five additional years of data are available for analysis, confirming the brightening trend that now extends to 15 years.…”
Section: Stellar Variabilitysupporting
confidence: 53%
See 1 more Smart Citation
“…Jao et al (2011) first reported the long-term variability of our parallax stars with coverage from 2-10 years and found that the 22 cool subdwarfs investigated at the time were substantially less photometrically variable than the 108 main sequence red dwarf examined. Hosey et al (2015) then expanded the variability study to 264 M dwarfs and found that only 8% of M dwarfs are photometrically variable by at least 20 mmag. Details of the data-reduction processes used to determine variability can be found in those two papers.…”
Section: Variability Resultsmentioning
confidence: 99%
“…However, there are several indications in the literature that this system is old. Hosey et al (2015) showed that it is very quiet with variation amplitudes of only 17.2 mmag in the optical. Its absolute magnitude is about 0.7 mag brighter than the main sequence, which could be an indication of youth, but this can be explained by its high metallicity alone (e.g., Neves et al 2013 measure [Fe/H] ≈ 0.12-40 dex).…”
Section: Rv Variable Targetsmentioning
confidence: 99%